Comparison of the antioxidant activities of nonfumigated and sulphur-fumigated Chrysanthemum morifolium cv. Hang-ju induced by oxidative stress. (1st January 2021) - Ma, Hongyan; Liu, Shanshan; Qu, Wenshan; Huang, Qi; Li, Linyuan; Chu, Fujiang; Zhu, Yuyun; Lv, Xinlin; Wang, Zhimin; Zhu, Jingjing
Abstract: Context: The traditional drying method, sun drying, for Chrysanthemum morifolium Ramat. cv. Hang-ju (Compositae) (HJ) is widely replaced by sulphur fumigation (SF), which has an unknown effect on its efficacy. Objective: To investigate protective effects of nonfumigated HJ (NHJ) and sulphur-fumigated HJ (SHJ) water extracts against oxidative stress and lipid peroxidation. Materials and methods: Sprague-Dawley rats were administered high-fat diet to induce hyperlipidaemia and randomly divided into eight groups ( n = 6): control, fenofibrate, NHJ and SHJ extracts (1, 2 or 4 g crude drugs/kg/d; intragastric administration for 8 weeks). Serum total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), superoxide dismutase (SOD) and malondialdehyde (MDA) levels were detected. Human umbilical vein endothelial cells (HUVECs) were treated with NHJ and SHJ extracts (50, 100 or 200 μg/mL) for 24 h, followed by oxidized low-density lipoprotein (ox-LDL, 20 μg/mL) for 2 h in vitro . Cellular reactive oxygen species (ROS), SOD and MDA levels and apoptosis were evaluated. Results: NHJ was more effective than SHJ in decreasing serum TG, TC, LDL-C, LDL/HDL and MDA while increasing serum HDL-C and SOD levels at high doses. SHJ (IC50 =19.9 mg/mL) suppressed HUVEC growth stronger than NHJ (IC50 =186.7 mg/mL). At 200 μg/mL, NHJ was more effective than SHJ in downregulating ROS and MDA levels, reducing HUVECs apoptosis rate and elevating SOD activity in ox-LDL-treated HUVECs. Conclusions: SF causes oxidative damage and attenuates antioxidative activity in ox-LDL-treated HUVECs, which promotes lipid peroxidation. SF is not recommended for processing HJ.